51 In vitro and in vivo activity of sacituzumab govitecan, in ovarian cancer. (18th September 2019) - Perrone, E; Lopez, S; Zeibek, B; Bellone, S; Zammataro, L; Manzano, A; Bonazzoli, E; Manara, P; Scambia, G; Santin, A
Abstract : Objectives: Epithelial ovarian cancer (EOC) is the most lethal gynecologic malignancy. Sacituzumab govitecan (SG) is a novel antibody-drug-conjugate (ADC) targeting trophoblast-antigen-2 (Trop-2), a cell surface glycoprotein highly expressed in many epithelial tumors, to deliver SN-38, the active metabolite of irinotecan. This study aimed to evaluate the efficacy of SG in primary EOC cell lines and xenografts. Methods: Trop-2 expression was evaluated in 90 formalin-fixed-paraffin-embedded (FFPE) tumors and 9 primary tumor cell lines by immunohistochemistry and flow cytometry, respectively. Trop-2 expression and cell viability after exposure to SG in primary tumor cell lines, non-targeting control-ADC (h679-CL2A-SN-38), and SG-parental antibody hRS7 IgG wereevaluated using flow-cytometry-based-assays. Antibody-dependent-cell-cytotoxicity (ADCC) against Trop-2+ and Trop-2- EOC cell lines was evaluated in vitro using 4-h Chromium-release-assays. In vivo activity of SG was tested againstTrop-2+ EOC xenografts. Results: Moderate-to-strong staining was seen in 47% (42/90) of ovarian tumors while 89% (8/9) of the primary EOC cell lines overexpressed Trop-2. EOC overexpressing Trop-2 were significantly more sensitive to SG compared to control ADC (p<0.05). Both SG and hRS7 mediated high ADCC activity only against Trop2+ cell lines. SGalso induced bystander killing of Trop-2- tumor cells. In vivo experiments with SG in EOC xenografts demonstrated greater antitumor effects and increased survival compared to ADC controls (p<0.05). SG was well tolerated by the animals. Conclusions: SG has shown remarkable preclinical activity against biologically aggressive EOC and it is endowed with significant bystander effect against tumors with heterogenous TROP-2 expression. Clinical trials are warranted.